Method Comparison of DNA Isolation and Quantification for Fish and Seafood Authenticity Determination - Dwiyitno Dwiyitno; Stefan Hoffman; Koen Parmentier; Chris Van Keer (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2018)
Fish and seafood products has been commonly targeted for fraudulent activities. For that reason, authentication of fish and seafood products is important to protect consumers from fraudulent and adulteration practices, as well as to implement traceability regulation. From the viewpoint of food safety, authenticity is beneficial to protect public from serious food poisoning incidents, such as due to ingestion of toxic species. Since DNA based identification depends on the nucleic acid polymerase chain reaction (PCR), the quantity and quality/purity of DNA will contribute significantly to the species authentication. In the present study, different DNA extraction and purification methods (3 classical methods and one commercial kit) were compared to produce the better isolated DNA for PCR amplification. Additionally, different methods for the estimation of DNA concentration and purity which is essential for PCR amplification efficiency were also evaluated. The result showed that classical DNA extraction methods (based on TNES-Urea) yielded a higher amount of DNA (11.30-323.60 ng/g tissue) in comparison to commercial kit/Wizard Promega (5.70-83.45 ng/g tissue). Based on the purity of DNA extract (A260/280), classical DNA extraction method produced relatively similar on DNA quality to the commercial kit (1.79-2.12). Interestingly, all classical methods produced DNA with A260/280 ratio of more than 2.00 on the blue mussel, in contrast with commercial kit. The commercial kit also produced better quality of DNA compared to the classical methods, showing the higher efficiency in PCR amplification. NanoDrop is promising as cheap, robust and safe UV-spectrophotometer method for DNA quantification, as well as the purity evaluation.Keywords: seafood authenticity, DNA isolation, polymerase chain reaction, NanoDrop, Picogreen